Effects of Different Organic Wastes at Varying Temperatures on Morphotypes of Nigerian Corchorus olitorius L - Lamidi, Wasiu Agunbiade; Ojeleye, Abiola; Abiola, Samson; Ojeokun, Olayemi (Asian Health, Science and Technology Reports, 2024)
This study investigated the effects of different types of organic wastes (poultry manure and cow dung) at varying temperatures (25 30, and 35°C) on the germination, growth, and yield responses of three morphotypes of Corchorus olitorius (Agbadu, Yaya, and Eleti’eku). The study was carried out at the Osun State University Teaching and Research Farms using a Completely Randomized Design (CRD) design with three-factor levels namely: two organic media, three morphotypes of C. olitorius and three soil temperatures at three replications to make 2 × 3 × 3 × 3 design. There was a control with loam soil in all the soil temperatures. Data were collected on the number of leaves, plant height, stem girth, number of branches, leaf weight, and leaf area index. The analysis of variance showed that the interaction of organic media, temperature, and morphotypes had significant effects on most of the traits evaluated (P<0.05). Poultry manure treatment (15 t/ha) significantly improved the vegetative parameters, the Agbadu morphotype showed the highest seed germination rate across all temperatures, while the Eleti’eku morphotype showed the lowest. Furthermore, the study revealed that the Agbadu morphotype exhibited superior germination performance when subjected to a temperature of 35°C and treated with poultry manure. These findings are significant for the development of new cultivars of C. olitorius that are tolerant to abiotic stress and can maintain high biomass production while reducing input resources.